The Urgency of Legal Education for Teachers to Prevent Teacher Criminalization in Learning - Sapto Budoyo; Marzellina Hardiyanti; Praditya Arcy Pratama (Yayasan Keluarga Guru Mandiri, 2023)
Teachers are educators who carry out their duties and obligations professionally. However, there is a clash between enforcing discipline to students and Law No. 35 of 2014 concerning Child Protection. The main problem in this research is analyzing the reasons for the need for legal education for teachers to prevent the criminalization of teachers in learning and government efforts to prevent the criminalization of teachers in learning. This research used a juridical-normative approach method with secondary data, which was analyzed deductively using descriptive-analytical data analysis. The results of the research and discussion show that legal education is needed for teachers to prevent criminalization because teachers receive protection through Law No. 14 of 2005 concerning Teachers and Lecturers and Law No. 20 of 2003 concerning the National Education System. The many conflicting cases of enforcing teacher discipline for students and the imposition of sanctions, which result in criminalization, encourage the need for legal education and legal understanding for teachers in Indonesia. Efforts that the government can make to prevent criminalization are providing legal outreach programs for teachers in Indonesia, strengthening legal protection regulations for teachers in learning, and providing character education to students.